CHEESES WITH ADDITIONS - Savić, Mirjana; Kljajić, Nataša; Arsić, Slavica (Economics of Agriculture, 2009)
In this paper work we show data about cheese production in world and in Serbia, different cheese sorts and different cheese addition in contexts of achieving specific season, nutritive and functional characteristics, especially from the aspects of official Statutes about quality and other requirement for milk, milk products, composite milk products and starter culture.